herman de vries - to be all ways to be exhibition 9 may - 22 november 2015, dutch pavillion, biennale arte 2015 - Martin, Jean Hubert 1944-; Vries, Herman de 1931-; Boer, Cees de 1955-; Huizing, Colin; Donker, Birgit 1965- (valiz, 2015)
The relationship between man, culture and nature is increasingly becoming a subject of (artistic) research within the visual arts a theme on which de vries (Alkmaar, NL, 1931) has been working for decades. For more than 60 years now he has been developing a highly versatile oeuvre in which art, science and philosophy are confronted with the worlds, and especially natures reality. The theme of his work is topical in an age in which ecological issues can count on an ever broadening attention from the general public. De vries recent work dominates his presentation in Venice, as it does in the book to be all ways to be. The books guideline is a dialogue between de vries and Jean-Hubert Martin about the works on show in Venice. Martin confronts de vries with key concepts such as synesthesis, mimesis, craftmanship, sound and music, smell, nature and ecology, et cetera, and interweaves the works and thoughts of de vries, with images, texts and other sources throughout his text. Exhibition: Biennale di Venezia, Italy (09.05-22.11.2015)
Keywords: Vries, Herman de 1931-; Vries, Herman de -- 1931-; Biennale di Venezia -- 56. -- 2015 -- Venedig; Installation -- Kunst; Ausstellungskatalog -- Giardini Pubblici -- 09.05.2015-22.11.2015 -- Venedig